Adolescentes em conflito com a lei: repercussão da pobreza multidimensional não monetária na criminalidade do Município de Wenceslau Braz - PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
There currently is an increasing number of infractions, especially of petty theft, which are offenses that involve seizing other people’s property without the use of violence or threat. In this context, this research intends to find whether a relation between crime and poverty exists. Firstly, considering that poverty cannot be conceived in the sense of mere lack of economic conditions, the term multidimensional is adopted, as in multidimensional poverty. This concept involves the deprivation of culture, leisure, quality education, health, and other elements capable of reflecting an eventual insufficiency of any minimum vital value for a quality life. The research is justified by the need for a scientific technical study that directly treats the relation between multidimensional poverty and crime, especially in terms of how they interact with infractions. The study analyzes the reality found in the town of Wenceslau Braz - PR, in the region known as Pioneer North in the State of Paraná. The town is located in a precarious area of the State, with no access to universities, professional training programs, income acquisition, job opportunities with perspectives of growth, and public cultural activities to engage the community. This work is limited to analyzing the effects of multidimensional poverty among adolescents, individuals in development that lack full cognitive capabilities and are more prone to influences from external factors, in the establishment of their judgment of what is right and wrong. Moreover, as developing individuals, they tend to let their impulses guide them in the attempt of gaining space in a highly-excluding society, driven by the capitalist market in which only a good buyer is seen as worthy of rights. The legislation has needed to evolve to keep pace with social evolutions, especially in the treatment of adolescents in conflict with the law, since they are either seen as victims of society, as subjects of rights, or objects of intervention, subject to State Power and to the will of the ruling class, capable of excluding and stigmatizing the citizen. This study also discusses the possible responsibility of the Democratic Rule-of-law State in this process of criminality, pointing that it should be considered co-culpable, that it, co-responsible. In order to fully develop its proposal, this research is descriptive, exploratory, quantitative, and in search of the subject through secondary information. It conducts analyses of the content of the interviews with the Public Prosecutor and Police Authority, of the data provided by the Court of Justice and the Brazilian Institute of Geography and Statistics, in addition to a bibliographic and document search submitted to content analysis in order to enable the final composition. As corollary has been researched on multidimensional gravity is not able to influence the criminalization of the issues under development. Areas of the city with a lower social infrastructure index, as a rule, more adolescents in conflict with the law, thoese who are in their ability to receive school, andy many no longer attend a school. Beings, other factores capable of influencing crime, as well as multidimensional, non-monetary poverty.
Keywords: Atos infracionais; Criminalidade; Pobreza multidimensional não monetária; Adolescentes em conflito com a lei; Infraestrutura social; Coculpabilidade; Infractions; Criminality; Multidimensional non-monetary poverty; Adolescents in conflict with the law; Social infrastructure; Coculpability; CNPQ::CIENCIAS SOCIAIS APLICADAS